(untitled) (Bangladesh Journal of Urology, 2020)
Objective: To compare the success rates and complications of Lithoclast and holmium laser-assisted ureterorenoscopy (URS) in managing ureteral stones. Material and Methods: We prospectively analyzed the records of 35 patients with ureteral stone who underwent ureteroscopic lithotripsy at our institution from January 2018 to February 2019. In 15 patients (mean stone size 12.6 mm), pneumatic lithotripsy was used; in 20 patients (mean stone size 11.6 mm), laser lithotripsy was performed. Patients were monitored as outpatients at 3 weeks and at 3 months with a kidneys, ureters, and bladder radiograph and ultrasonography. Patients with migrated stones or incomplete clearance underwent an auxiliary procedure such as shockwave lithotripsy (ESWL) or repeated URS. Results: Successful fragmentation included complete stone clearance seen on a KUB radiograph or USG at 3 weeks after URS. This occurred in 11/15 (73.3%) patients in the Lithoclast group and in 18/20 (90%) in the laser group. Auxiliary procedures included ESWL 2 patients in the Lithoclast group and 1 patient in the laser group) or repeated URS (two in the Lithoclast group). Urosepsis after URS occurred in 2/15 (13.3%) patients in the Lithoclast group and 2/20 (10.0%) patients in the laser group. Conclusion: In our study, the fragmentation rates of holmium laser-assisted ureteroscopy were significantly better. The complications and the need for auxiliary procedures were significantly less for holmium laser-assisted ureteroscopy when compared with pneumatic lithotripsy. Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.36-40